2011
DOI: 10.1111/j.1447-0756.2010.01422.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant activated factor VII as a promising adjuvant therapy for postpartum hemorrhage in the practice of obstetric anesthesia: Experience from a university hospital in Taiwan

Abstract: Massive postpartum hemorrhage is one of the major complications in the peripartum period. In some critical cases, hemostasis is hard to achieve even after a hysterectomy has been performed. Recombinant activated factor VII has been reported as a promising adjuvant therapy for obstetric hemorrhage, although it remains unlicensed for this indication. Eight cases receiving recombinant activated factor VII in postpartum hemorrhage refractory to the conventional therapy in a Taiwanese hospital were analyzed retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(117 reference statements)
1
4
0
1
Order By: Relevance
“…24 In this study, all patients received a single dose 80 μg/kg or 85 μg/kg of rFVIIa. Jan et al reported good responses with a single dose of rFVIIa ranging from 55-105 μg/kg body weight (average 77.13 μg/kg) 23 , similar dose to this study.…”
Section: Pph Patients and Australian And New Zealandsupporting
confidence: 88%
See 1 more Smart Citation
“…24 In this study, all patients received a single dose 80 μg/kg or 85 μg/kg of rFVIIa. Jan et al reported good responses with a single dose of rFVIIa ranging from 55-105 μg/kg body weight (average 77.13 μg/kg) 23 , similar dose to this study.…”
Section: Pph Patients and Australian And New Zealandsupporting
confidence: 88%
“…26 Welsh et al recommended that If, after 20 minutes, there is no increasing number of case reports where empirical 'off-label' use of rFVIIa has been effective in the treatment of massive PPH which did not respond to conventional methods. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Since the action of rFVIIa is limited to the site of tissue injury and tissue factor exposure, administration of rFVIIa is con sidered to be particularly useful in an obstetric setting where there is often bleeding from a large raw area of exposed tissue. 4 Latest reports from the Italian Registry regarding…”
Section: Resultsmentioning
confidence: 99%
“…Substitution using 4 g FC may be insufficient for such severe obstetric DIC. Recently, rFVIIa has been reported to be effective in managing life‐threatening obstetric hemorrhage . Because fibrinogen is essential for the response of rFVIIa, fibrinogen substitution may immediately assist the effectiveness of administered rFVIIa.…”
Section: Discussionmentioning
confidence: 99%
“…Eight cases receiving recombinant activated factor VII in postpartum haemorrhage refractory to the conventional therapy in a Taiwanese hospital were analyzed retrospectively. 32 A good response, defined as bleeding control in 15 minutes was achieved in 6 patients (75%) with a single dose ranging from 55 to 105ugm/kg. The 2 patients with poor response had unsolved birth canal injuries.…”
Section: Use In Obstetric Haemorrhagementioning
confidence: 93%
“…If rFVIIa is administered early, not only a hysterectomy but also the surgery related complications may be prevented. 32 In situations of intractable PPH, where a hysterectomy is otherwise not indicated, administration of rFVIIA can be considered as soon as possible in a few special situations: when blood is not available, in patients with acquired haemophilia, before packing the uterus or pelvis, before considering surgical procedures like peripartum hysterectomy or laparotomy(especially in cases of vaginal delivery). In cases with actively bleeding vaginal lacerations, especially in patients brought in some time after delivery and the vaginal mucosa has become edematous and not amenable to haemostasis and suturing, rFVIIa should be considered early in management before patients condition worsens and she starts slipping out of hands.…”
Section: Timing Of Usementioning
confidence: 99%